A Systematic Review of the Effectiveness of Core Stability Exercises in Patients with Non-Specific Low Back Pain - Zachary Smrcina; Sarah Woelfel; Christopher Burcal (North American Sports Medicine Institute, 2022)
# Background Low back pain affects millions of people worldwide and can be a difficult condition to manage clinically. Many cases do not have a discernable etiology, further increasing the complexity of finding an effective intervention. Core stabilization exercises (CSE) strengthen the musculature that provides stability to the spine and show promising outcomes. # Purpose To examine the efficacy of CSE exercises in the treatment of NSLBP in adult patients. # Study Selection Studies were included if they had patients diagnosed with NSLBP, used CSE as a treatment for NSLBP, and were a clinical trial. Exclusion criteria were studies that did not utilize an objective pain scale, patients who had a specific diagnosed pathology contributing to the NSLBP or received treatment for their NSLBP within the prior six months. # Methods The literature was systematically searched in the PubMed, Sports Medicine & Education Index, and CINHAL databases, using the search terms core stabilization, low back pain, and exercise. The initial search yielded 229 articles and was refined using search terms 'NOT analysis' in order to target randomized control trials and exclude meta-analyses to narrow the search. Full-text of the articles were assessed for eligibility by utilizing inclusion and exclusion criteria that were included in this review. Articles were assessed for quality using the PEDro scale and relevant data were extracted. # Results Five moderate-quality studies (PEDRO range: 5-8) support CSE is an effective method to decrease pain, improve functionality, and increase core strength in patients with NSLBP. Although there are other commonly used methods to treating NSLBP, CSE have shown to be a beneficial method to treating NSLBP. # Conclusion Grade B evidence suggests core stabilization exercises can be considered a favorable method for treating pain in patients with NSLBP. # Level of Evidence 1b